Penggerusan di Hilir Bendung dengan Mercy Type Vlugter - Sutandi, Maria Christine; Tjandrapuspa, Kanjalia; Husada, Ginardy (Jurnal Teknik Sipil, 2019)
Indonesia is a developing tropical country. With abundant natural resources, especially water resources, as well as the conditions of agrarian society so that the agricultural sector has great potential and should be developed in Indonesia. To support this, we need a network of irrigation to irrigate the irrigation network of the source is a river located upstream of the dam that required manufacture of the river water level can be elevated, with the aim to reach a wider area of rice fields. The stability of the weir is affected by scour downstream of the weir, so there should be research scouring downstream of the weir, in this study we used 2 type weir with 2 radius Summit of Vlugter and the body of dam with slope 1: 1 and 3.5: 4. Having conducted research with a variety of discharge through, showed that scour downstream weir smallest body caused by tilting weir 3.5: 4 but it also is the benefit of this study as a model to be followed up with a prototype.